The Conservation of Races - Du Bois, W. E. B. (William Edward Burghardt), 1868-1963 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Conservation of Races" by W. E. B. Du Bois is a scholarly publication written in the late 19th century. This work dives into the complex topic of racial identity and the historical significance of race in shaping human civilization. Du Bois presents a worldview that emphasizes the need for the African American community to nurture its own identity and strive for collective advancement. In this insightful text, Du Bois explores the intricate nature of racial distinctions and their impact on social structures and individual identities. He highlights the ongoing racial struggles faced by African Americans and argues for the importance of recognizing the distinct contributions of the Negro race to civilization. By advocating for solidarity and organized efforts within the race, he calls for pride in racial identity while simultaneously proposing a path toward mutual respect and cooperation among races. Additionally, Du Bois outlines the responsibilities of educated African Americans in uplifting their communities through self-improvement, moral integrity, and the assertion of their place within the broader American society. Through this nuanced discussion, Du Bois provides a foundation for understanding the intersection of race, culture, and progress in a racially diverse nation. (This is an automatically generated summary.)
Release date is 2004-05-01
This eBook was produced by Stephanie McNees
Keywords: African Americans -- Social conditions; United States -- Race relations; African Americans -- Race identity